Menguatkan Pendidikan Islam dan Edukasi Digital Mahasiswa: Eksploring Pengaruh Komunikasi Pemasaran dan Media Sosial Instagram terhadap Brand Awareness - Alfasi, Shebian; Sudirman, Iman Fauzi; Mubarok, Diki (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
This study aims to analyze the influence of marketing communication and Instagram social media on brand awareness in the local culinary business PaPa Burjo and its implications for strengthening digital education from the perspective of Islamic Education. The research employs a quantitative approach using a survey method involving 100 respondents who are consumers of PaPa Burjo, selected through purposive sampling. Data were collected using structured questionnaires and analyzed using multiple linear regression with SPSS version 26. The results indicate that marketing communication and Instagram social media simultaneously and partially have a significant effect on brand awareness, with Instagram social media showing a more dominant influence. These findings confirm that ethical, creative, and informative digital communication strategies align with the values of Islamic Education, particularly honesty (ṣidq), responsibility (amānah), and consumer education. This study contributes both theoretically and practically to the development of digital literacy and value-based marketing communication among students and local entrepreneurs within an Islamic educational framework.